Ranking the performance of national innovation systems in the Iberian Peninsula and Latin America from a neo-Schumpeterian economics perspective - Harold Paredes-Frigolett; Andreas Pyka; Javier Pereira; Luiz Flávio Autran Monteiro Gomes (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
We present the results of an empirical study of the national innovation systems of countries in the Iberian Peninsula and Latin America from a comprehensive neo-Schumpeterian economics (CNSE) perspective. The empirical study covered the period from 2000 until 2011 and the countries analyzed are Argentina, Brazil, Chile, Mexico, Portugal, and Spain. Unlike previous approaches that used cluster analyses as a methodological framework to analyze national innovation systems from a CSNE perspective, we use a novel approach based on multicriteria decision analysis (MCDA) to rank innovation performance. We show how an MCDA approach can be followed in order to rank the performance of national innovation systems and provide an analysis of the results obtained at the financial, public and industry pillars of the CNSE model.
urn:nbn:de:bsz:100-opus-10288
Keywords: 330; Comprehensive neo-Schumpeterian Economics; Innovation Performance; Multicriteria Decision Analysis; National Innovation Systems; China